Political or Religious Policy? Indigenous Christian Education in the Dutch East Indies Era - Juwono, Harto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This study is a textual analysis discussing the existence of Christian educational institutions for indigenous students under the Dutch colonial administration in the Dutch East Indies. The primary objective of this research is to examine the underlying motives behind the Dutch colonial government’s policies on Christian education for indigenous communities, specifically to determine whether these policies were politically or religiously motivated. Focusing on historical contexts, this research employs historical methods to reconstruct past events. The central question addressed is the Dutch colonial government’s main focus in shaping policies for Christian education through mission institutions for indigenous communities: whether these were driven by political interests or religious considerations. Data sources were obtained from literature and historical documents archived in data storage centers and libraries. The findings, using a structuration methodology, reveal a pragmatic dualism underlying the colonial government’s policies, which shifted according to the socio-political context.